Tourism Management System - Peter Wamoni (Uganda Christian University, 2025)
Tourism Management System is a complete trust fully integrated tourism web site. The web site covers all the areas required for an including tourism. This project is developed to manage the tourist in the tourism management web site. The main module in this project are login tourist management complaints and reports. The project is to develop a system that automates the process and activities of travel and. The purpose is to design a system using which one can perform all operations related to travelling. In the present a customer has to approach various agencies to find details of places and book tickets. This often requires a lot of time and effort. A customer may not get a desired information from the offices and often the customer may be misguided. It is tedious for customer to plan a particular journey and have it executed properly. Therefore, the proposed system is a web-based application and maintains a centralized repository of all related information. The system allows one to easily access the relevant information and make necessary travel arrangements. Users can decide about places they want to visit and make booking online for travel and accommodations.
Undergraduate Research